SAT0180 EVALUATION OF FRAILTY IN SJÖGREN'S SYNDROME: CREATION OF A FRAILTY INDEX. (June 2019) - Izzo, Raffaella; Canevelli, Marco; Colafrancesco, Serena; Minniti, Antonina; Gattamelata, Angelica; Arienzo, Francesca; Quarata, Federica; Remiddi, Francesca; Raparelli, Valeria; Bruno, Giuseppe; Priori, Roberta; Valesini, Guido
Abstract : Background: Frailty is a condition characterized by the reduction of the individual's homeostatic reserves, leading to an increased vulnerability to stressors and an increased risk of unfavourable events. The aging of the population and the consequent need to implement new paradigms of care and assistance, have given this tool a growing interest in many medical disciplines 1 . In rheumatology, however, the interest is still limited 2 . The Frailty Index (FI), developed on an arithmetical model of deficit accumulation, is an accurate tool for assessing frailty, providing an estimate of the biological aging. Objectives: Creation of a FI to be used in clinical practice in patients with Sjögren's syndrome (SS) and evaluation of the correlations with patient's age, duration of illness, activity and disease damage at baseline and in the following 5 years. Methods: The FI is composed by a checklist of non-predefined variables (deficits) constituted by symptoms, signs, diseases, disabilities, and laboratory findings. The deficits must meet these criteria: age-related; associated with negative outcomes; multidimensional (referring to different domains of the health status); present in at least 1%, but not more than 80% of the sample. To each variable is assigned the value of 0 (= no deficit) or 1 (= deficit). The FI is the ratio between deficits presented by the individual and the total number of deficits considered, thus providing a measure of frailty ranging between 0 (no frailty) and 1 (maximum of frailty) 3 . A FI was developed for patients with SS consisting of 43 items (17 comorbidities, 14 signs and symptoms, 5 disabilities and 7 laboratory findings). Statistical analysis was performed with Spearman's test for correlation assessment, the Mann Whitney test for comparing non-parametric variables was used. Results: FI was administered to a first small group of 30 female consecutive patients recruited as outpatients at the clinic dedicated to SS. The average age was 57.2 yrs, mean age at diagnosis 52.7 yrs and average disease duration 4.7 yrs. At the time of completing the FI, the average disease activity (ESSDAI) was 3.4, the mean value of the damage (SjSDDI) 1.6 and the average score of FI equal to 0.21. A statistically significant correlation between FI and age has been reported (p = 0.017). No significant correlations between frailty and duration, activity and disease damage have been highlighted at the moment. Conclusion: For the first time a FI was developed for patients with SS consisting of 43 items. The data shows a relationship between age andFI. The correlation is statistically significant, similarly to what is reported in the literature for other conditions. This confirms that FI is indeed an objective marker of aging and even though the sample population is young (average age = 57.2 years), FI maintains its main properties. This tool can be used to assess the health status of patients, making it possible to identify those at greater risk of trajectories or unfavourable outcomes. It is currently being administered the FI to patients with SS whose clinical course will be evaluated in the next 5 years (complications, mortality, hospitalization, institutionalization and disability). References: [1] Canevelli M, et al, Promoting the Assessment of Frailty in the Clinical Approach to Cognitive Disorders, Front. Aging Neurosc 2017 [2] Rockwood MR, et al, FI to Measure Health Status in People with SSc, J Rheum 2014 [3] Searle SD, et al, A standard procedure for creating a FI, BMC Geriatrics2008 Disclosure of Interests: None declared